Estradiol increases dendritic length and spine density in CA1 neurons of the hippocampus of spontaneously hypertensive rats: A Golgi impregnation study - Brocca, María Elvira (2013)
Increased neuronal vulnerability has been described in the brain of spontaneously hypertensive rats (SHR), models of primary hypertension. Previous data indicate that estradiol treatment corrects several dysfunctions of the hippocampus and hypothalamus of SHR. Considering this evidence we analyzed the dendritic arborization and spine density of the CA1 subfield in SHR and Wistar-Kyoto (WKY) normotensive rats with and without estradiol treatment. Five month old male SHR and WKY rats received single estradiol or cholesterol pellets (sham treatment) for 2 weeks. A substantial rise of circulating estradiol (>25 fold) and testicular atrophy was present in all estradiol-receiving rats. In both SHR and WKY rats, estradiol decreased blood pressure by ~20 mm Hg; however, a moderate hypertension persisted in SHR (164 mm Hg). Using a modified Golgi impregnation technique, apical and basal dendrites of the CA1 subfield were subjected to Sholl analysis. Spine density was also statistically analyzed. Apical dendritic length was significantly lower in SHR compared to WKY rats (p<0.01), whereas estradiol treatment increased dendritic length in the SHR group only (SHR vs SHR+estradiol; p<0.01). Apical dendritic length plotted against the shell distances 20-100, 120-200 and 220-300 μm, revealed that changes were more pronounced in the range 120-200 μm between SHR vs. WKY rats (p<0.05) and SHR vs. SHR+estradiol (p<0.05). Instead, basal dendrites were not significantly modified by hypertension or steroid treatment. Spine density of apical dendrites was lower in SHR than WKY (p<0.05) and was up-regulated in the SHR+estradiol group compared to the SHR group (p<0.001). Similar changes were obtained for basal dendritic spines. These data suggest that changes of neuronal processes in SHR are plastic events restorable by estradiol treatment. In conjunction with previous results, the present data reveal new targets of estradiol neuroprotection in the brain of hypertensive rats.